O papel de enfermeiros na equipe multidisciplinar frente ao sobrepeso/obesidade em ambiente de trabalho - Demorais, Irenilde Carvalho; Santos, Lui Felipe Puppin dos [UNESP]; Souza, Cecilia Alves de [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Miranda, Regina Márcia Vicente Silveira; Brasilino, Matheus da Silva [UNESP]; Miranda, Ricardo Cabral; Garcia, Sérgio Diniz [UNESP]; Kaneto, Carlos Noriyuki [UNESP]; Silveira Neto, Luiz da [UNESP] (My University, 2014)
Overweight and obesity are pandemics and have been widely discussed in Public Health and Health at Work. Comorbidities such as metabolic syndrome, hypertension, diabetes mellitus type 2, orthopedic disorders and coronary diseases can induce to absenteeism, reduced work performance, disability and death. The aim of this review is to discuss the role of the nurse in control and prevention of these illnesses in the workplace. We concluded that occupational health nurses work should act proactively with a multidisciplinary team aimed at individual and collective monitoring of actions designed to control and prevent overweight and obesity. Furthermore, this professional should follow up the health of individual workers with a high body mass index in order to warn and prevent comorbidities related to these conditions.

El sobrepeso y la obesidad son una pandemia y han sido ampliamente discutido en Salud Pública y Salud en el Trabajo. Las comorbilidades tales como el síndrome metabólico, la hipertensión, la diabetes mellitus tipo 2, trastornos ortopédicos y enfermedades coronarias pueden causar ausentismo, el desempeño laboral reducido, discapacidad y muerte. El objetivo de esta revisión es discutir el papel de la enfermera en el control y la prevención de estas enfermedades en el lugar de trabajo. Llegamos a la conclusión de que el trabajo de la enfermera es actuar de forma proactiva a un equipo multidisciplinar orientado a lo seguimiento individual y colectiva de las acciones emprendidas en el control y la prevención del sobrepeso y la obesidad. Por otra parte, debe acompañar a la salud de los trabajadores individuales con un alto índice de masa corporal con el fin de advertir y prevenir las comorbilidades en esta condición.

O sobrepeso e a obesidade são uma pandemia e têm sido amplamente discutidos em Saúde Pública e Saúde no Trabalho. Comorbidades como síndrome metabólica, hipertensão arterial, diabetes mellitus do tipo 2, alterações ortopédicas e doenças coronarianas podem causar absenteísmo, redução de rendimento laboral, incapacitação e morte. O objetivo desta revisão de literatura é discutir o papel do enfermeiro no controle e prevenção dessas morbidades em ambiente de trabalho. Nós concluímos que o enfermeiro do trabalho deve atuar de forma proativa junto a uma equipe multidisciplinar visando ao monitoramento individual e coletivo das ações desenvolvidas no controle e na prevenção do sobrepeso e da obesidade. Além disso, deve acompanhar individualmente a saúde de trabalhadores com elevado índice de massa corporal com o intuito de alertar e prevenir sobre as comorbidades dessa condição.
The role of nurses in the multidisciplinary team against overweight / obesity in workplace
El papel de la enfermera en el equipo multidisciplinar contra el sobrepeso / obesidad en el lugar de trabajo
Keywords: Occupational health nursing; Occupational exposure; Prevention & control; Public health; Enfermería del trabajo; Exposición profesional; Prevención & control; Salud pública; Enfermagem do trabalho; Exposição ocupacional; Prevenção & controle; Saúde pública